STUDI ADSORPSI ION Pb2+ MENGGUNAKAN JERAMI PADI OLAHAN ASAL MANOKWARI - Jacson Victor Morin; Darma Santi (Jurnal Natural, 2008)
The waste material of agriculture such as the straw of rice was not yet used maximal as the kind of the materials for solution of environment pollution problem. Until this moment, there was any kind of ways that was done for separated the heavy metal from waste water, include the physical, chemistry and biology methods. Study of ion Pb2+ absorption using treated rice straw was carried out to determine the absorption of heavy metal from water. The result shows absorption of heavy Cr3+ > Pb2+ > Cu2+. The absorption interaction between Pb2+ ion and treated straw shows Langmuir pattern with maximum capacity of Pb2+ ions using the straw of rice was 52,083 mg Pb2+ /g the rice straw.